Molecular Detection of FIPV among Imported Felines through Soekarno Hatta Airport, Indonesia - Fitrawati, Fidyah; Suwarno; Yudaniayanti, Ira Sari; Rahmahani, Jola; Yunus, Muchammad; Soeharsono; Karo-karo, Desniwaty; Haeriah (Universitas Airlangga, 2025)
One of the viruses that can cause disease in cats is feline coronavirus (FCoV). This virus is often divided into type I and type II. Type I is a highly pathogenic strain, feline infectious peritonitis virus (FIPV). Type II is a milder strain, feline enteric coronavirus (FECV). The FIPV variant is said to be a result of a mutation from FECV. FIP disease is responsible for 0.3%-1.4% of cat deaths in veterinary clinics. This study aims to determine if there is an FIPV in imported cats at Soekarno Hatta Airport, Indonesia. Samples were taken from 15 imported cats from Russia and Vietnam. These two countries were chosen based on previously unreported cases. The samples, consisting of blood and rectal swabs, were tested molecularly using RT-PCR. Four samples from rectal swabs showed positive results with a single band at 677 bp. Two positive samples, namely 123v and 682v, were further sequenced. The study results indicate that the FCoV virus can be found in asymptomatic imported cats. Further research is needed to better understand the mechanism causing genetic diversification of FCoV or FIPV and its impact on the pathogenesis of FIP. Furthermore, the application of FIP vaccines from other countries should be tested for compatibility with the FIPV strains present in Indonesia.